AL amyloidosis: The effect of fluorescent in situ hybridization abnormalities on organ involvement and survival. (21st December 2020) - Ozga, Michael; Zhao, Qiuhong; Benson, Don; Elder, Patrick; Williams, Nita; Bumma, Naresh; Rosko, Ashley; Chaudhry, Maria; Khan, Abdullah; Devarakonda, Srinivas; Kahwash, Rami; Vallakati, Ajay; et al.
Abstract: Background: Systemic light chain (AL) amyloidosis is a clonal plasma‐cell neoplasm that carries a poor prognosis. Although AL amyloidosis and Multiple Myeloma (MM) can co‐exist and share various cytogenetic chromosomal abnormalities, little is known about Fluorescent in situ hybridization (FISH) and its prognostic relevance in AL amyloidosis. Aim: The study aims to evaluate the most prevalent FISH cytogenetic abnormalities in AL patients as independent prognostic factors, and assess the impact of cytogenetics on the survival of high‐risk cardiac AL patients. Materials & Methods: This retrospective study reviewed 113 consecutive AL patients treated at The Ohio State University (OSU). Patients were divided into subgroups based on FISH data obtained within 90 days of diagnosis. Hyperdiploidy was defined as trisomies of at least 2 chromosomal loci. Primary endpoints were progression free survival (PFS) and overall survival (OS). Kaplan Meier curves were used to calculate PFS and OS. The log‐rank test and Cox proportional hazard models were used to test the equality of survival functions and further evaluate the differences between groups. Results: FISH abnormalities were detected in 76% of patients. Patients with abnormal FISH trended toward lower overall survival (OS) (p=0.06) and progression free survival (PFS) (p=0.06). The two most prevalent aberrations were translocation t(11;14) (39%) and hyperdiploidy‐overall (38%). Hyperdiploidy‐overall was associated with worsening PFS (p=0.018) and OS (p=0.03), confirmed in multivariable analysis. Patients with del 13q most frequently had cardiac involvement (p=0.006) and was associated with increased bone marrow plasmacytosis (p=0.02). Cardiac AL patients with no FISH abnormalities had much improved OS (p=0.012) and PFS (p=0.018) Conclusions: Our findings ultimately reveal the association of hyperdiploidy on survival in AL amyloidosis patients, including the high‐risk cardiac AL population. Abstract : Hyperdiploidy in AL amyloidosis patients was associated with poor PFS and OS and cardiac AL patients had a strong association with del 13q.